The Influence of Financial Literacy and Financial Inclusion on the Sustainability of MSMEs in Kudus Regency - Dzulqornain Nasyrudin; Bonnix Hedy Maulana; Sukma Wijayanti (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the influence of financial literacy and financial inclusion on the business sustainability of Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector in Kudus Regency. MSMEs play an important role in regional economic development, employment creation, and income distribution; however, many culinary MSMEs continue to face challenges related to financial management, limited access to formal financial services, and long-term business sustainability. This study employed a quantitative approach using a descriptive correlational design with a cross-sectional method. A total of 115 respondents were selected through probability sampling techniques to ensure representative data. Data collection was conducted using structured questionnaires, while data analysis involved descriptive statistics, validity and reliability testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing. The findings reveal that financial literacy and financial inclusion have a positive and significant effect on the sustainability of culinary MSMEs, both partially and simultaneously. The Adjusted R Square value of 0.517 indicates that 51.7% of business sustainability is explained by the two independent variables, while the remaining percentage is influenced by other factors outside the model. These findings highlight the importance of strengthening financial knowledge and expanding access to financial services to support sustainable MSME development in Kudus Regency and improve long-term business competitiveness significantly.